Effect of social mobile commerce on Apple brand loyalty - Morteza Moradi, Paria Heidari, Alireza Aghighi, (Opción, 2019)
The purpose of this study is to examine the effect of mobile social commerce on brand loyalty among Apple brand customers in the Tehran’s Paitakht Complex. Data collection method was a researcher-made questionnaire (Likert scale) and validated by Alpha test. We concluded that the emphasis on customer expectations of up to 45% is predictive of perceived usefulness and up to 39% has the predictability of customer satisfaction, and a significant and positive relationship with both of them. Finally, it can be concluded that mobile social commerce is effective on brand loyalty in customers.